Isatuximab plus carfilzomib and dexamethasone versus carfilzomib and dexamethasone in relapsed multiple myeloma patients with renal impairment: IKEMA subgroup analysis - Capra, Marcelo; Martin, Thomas; Moreau, Philippe; Baker, Ross; Pour, Ludek; Min, Chang-Ki; Leleu, Xavier; Mohty, Mohamad; Segura, Marta Reinoso; Turgut, Mehmet; LeBlanc, Richard; Risse, Marie-Laure; et al. (Haematologica, 2022)
Renal impairment (RI) is common in patients with multiple myeloma (MM) and new therapies that can improve renal function are needed. The phase III IKEMA study (clinicaltrials gov. Identifier: NCT03275285) investigated isatuximab (Isa) with carfilzomib and dexamethasone (Kd) versus Kd in relapsed MM. This subgroup analysis examined results from patients with RI, defined as estimated glomerular filtration rate <60 mL/min/1.73 m². Addition of Isa prolonged progression-free survival (PFS) in patients with RI (hazard ratio: 0.27; 95% confidence interval [CI]: 0.11-0.66; median PFS not reached for Isa-Kd versus 13.4 months for Kd [20.8-month follow-up]). Complete renal responses occurred more frequently with Isa-Kd (52.0%) versus Kd (30.8%) and were durable in 32.0% versus 7.7% of patients, respectively. Treatment exposure was longer with Isa-Kd, with median number of started cycles and median duration of exposure of 20 versus 9 cycles and 81.0 versus 35.7 weeks for Isa-Kd versus Kd, respectively. Among patients with RI, the incidence of patients with grade ≥3 treatment-emergent adverse events was similar between the two arms (79.1% in Isa-Kd vs. 77.8% in Kd). In summary, the addition of Isa to Kd improved clinical outcomes with a manageable safety profile in patients with RI, consistent with the benefit observed in the overall IKEMA study population.
Keywords: Oligopeptides; renální insuficience; protokoly protinádorové kombinované chemoterapie; humanizované monoklonální protilátky; lidé; Multiple Myeloma; Antibodies, Monoclonal, Humanized; oligopeptidy; mnohočetný myelom; Renal Insufficiency; dexamethason; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Humans